Evaluasi Perspektif Pengguna Terhadap Sistem Informasi Pemerintahan Daerah (Studi Kasus di Kabupaten X) - Subroto, Imam; A. A. Uliansyah, Beta (Polytechnic of State Finance STAN, 2023)
Changing the SIMDA application to SIPD requires operators to adapt. This research aims to evaluate the implementation of SIPD in District X using the System Usability Scale (SUS) method and the Delone and Mclean Success Model. Then to find out which parts must be maintained and which must be improved using the Delone and Mclean Success Model. This research uses a mix method, through quantitative analysis using descriptive statistics followed by qualitative analysis using interviews. There are three types of information systems in SIPD, regional development information systems, regional financial information systems, and other regional government information systems. The SUS results show that these three types of SIPD have not been fully accepted by operators. An information system that is considered to be newly implemented is one of the factors why this information system has not been well received by users. The results of the analysis using the DeLone and McLean success model also show results that support the SUS analysis. The aspect that received the lowest score was the quality aspect of the information system. Meanwhile, the aspect that is considered the most satisfying is the service quality aspect. Services in the form of technical guidance have been provided by SIPD developers, but this needs to be done intensively, especially if there is an update to the information system. The suggestion from this research is that SIPD developers should provide more intensive technical guidance to operators and develop SIPD so that it is integrated with other applications.